Xylitol treats nasal mucosa in rhinitis medicamentosa: an experimental rat model study - (:unkn) unknown (SPRINGER, 2019)
Objective Rhinitis medicamentosa is drug-induced rhinitis which occurs by prolonged and overdose usage of topical nasal decongestants. There is not much of treatment choice rather than nasal steroids. In this pathological study, we have been aimed to represent the healing effects of xylitol on damaged nasal mucosa due to rhinitis medicamentosa. Method 30 Wistar rats were separated into 5 groups. During 2 months, oxymetazoline was given to the first group, and saline was given to second group intranasally. First and second group animals were examined at the end of 2 months and rhinitis medicamentosa was detected. Oxymetazoline was given to the third, fourth, and fifth groups during 2 months. Then xylitol solution, mometasone, and saline were applied, respectively, for 15 days. After the experiment, rats' nasal mucosas were evaluated histopathologically. Results Xylitol and mometasone were found to be more effective than the control group in terms of histopathological changes. Effectivity of xylitol and mometasone was compared and not a significant value was determined. Conclusions According to the results, xylitol solution is effective as mometasone, usable and well-priced in the treatment of rhinitis medicamentosa. More comprehensive and ultrastructural studies on animals and human studies with rhinometric evaluation should be performed.
Keywords: Rhinitis medicamentosa; Xylitol; Mometasone; Nasal mucosa; Nasal decongestants